Assessment of the strength reliability of high-temperature heat exchangers with long service life at the design stage (Fracture and Structural Integrity, 2020)
The article describes a method for assessing the strength reliability of high-temperature heat exchangers with service life of several tens of thousands of hours at the design stage, when there is not enough statistical data on the operating time of elements and material properties. The method shows, how to determine the missing coefficients of variation for calculating reliability and build the function of the probability of failure-free operation, considering the change of the properties of the structural material over time. The method of visualizing the distribution of zones, both satisfying and not satisfying reliability criteria at the nodes of any finite element model, is also described.
Keywords: Reliability; Strength; Heat-exchanger; Assessment